Effects of Sowing Dates and Cultivars on Protein and Mineral Contents of Bean (Phaseolus vulgaris L.) - Ceyhan, Ercan; Harmankaya, Mustafa; Ali Avci, Mehmet (Asian Journal of Chemistry, 2010)
Six bean cultivars were grown at four different sowing dates for two years to study the effects of sowing date, genotypic and growing seasons on protein and mineral contents. The protein and mineral contents of bean are influenced by growing seasons, sowing date and genetic factors. This study investigated differences in protein and mineral contents in grains of six bean (Phaseolus vulgaris L.) cultivars. Protein content ranged 21.40-27.29 %, phosphorus 570.00-796.59 mg/100 g, potassium 1856.40-2159.24 mg/100 g, magnesium 174.56-197.95 mg/100 g, calcium 120.06-182.65 mg/100 g, sodium 45.57-51.89 mg/100 g, iron 6.50-8.41 mg/100 g and zinc 1.69-2.27 mg/100 g, respectively with significant differences among bean cultivars. The effects of years, sowing date, cultivars, year × cultivars interaction, year × sowing date interaction, cultivars × sowing date interaction and year × cultivars × sowing date interaction were highly significant, but the variation was mainly attributed to the environment and sowing date. In general, protein, phosphorus, potassium, calcium, sodium and iron content increased with delayed sowing. Unlike, the zinc content decreased with delayed sowing.